THE ROLE OF SOCIAL WORKERS IN THE DEVELOPMENT OF TOURISM VILLAGES - Avid Leonardo Sari (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2017)
The description of the role of social workers is considered important because the initiator of the formation of a village tourism program in Sukaratu Village is the social worker itself, so that if the role can be fully described it is not impossible the role of social workers. In the village of Sukaratu can be adopted by other communities in different regions that have the same commitment to community development. These findings indicate that the role of community social workers at the identification stage is more facilitative and educative. At the socialization stage, the role of social workers is more dominant in practicing the role of representation and education. Subsequent roles in the social worker planning stage play a more facilitative role and in the implementation stages of social workers practice more training (educational) skills. Then at the evaluation stage the social worker does not perform a representational role, but rather performs a facilitation role to facilitate the evaluation procedure and the various aspects that must be in the evaluation process. While the barriers experienced by social workers in implementing the community development process in Sukaratu Village is in increasing the number of people involved in the implementation of representational roles.